Bisulfite Amplicon Sequencing Can Detect Glia and Neuron Cell-Free DNA in Blood Plasma - Zac Chatterton; Zac Chatterton; Zac Chatterton; Zac Chatterton; Zac Chatterton; Natalia Mendelev; Natalia Mendelev; Natalia Mendelev; Natalia Mendelev; Sean Chen; Sean Chen; Sean Chen; et al. (Frontiers in Molecular Neuroscience, 2021)
Sampling the live brain is difficult and dangerous, and withdrawing cerebrospinal fluid is uncomfortable and frightening to the subject, so new sources of real-time analysis are constantly sought. Cell-free DNA (cfDNA) derived from glia and neurons offers the potential for wide-ranging neurological disease diagnosis and monitoring. However, new laboratory and bioinformatic strategies are needed. DNA methylation patterns on individual cfDNA fragments can be used to ascribe their cell-of-origin. Here we describe bisulfite sequencing assays and bioinformatic processing methods to identify cfDNA derived from glia and neurons. In proof-of-concept experiments, we describe the presence of both glia- and neuron-cfDNA in the blood plasma of human subjects following mild trauma. This detection of glia- and neuron-cfDNA represents a significant step forward in the translation of liquid biopsies for neurological diseases.